2016
DOI: 10.1177/1073191115599639
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Equivalence of the K6 Scale

Abstract: This study examined the measurement equivalence of the K6 across diverse racial/ethnic and linguistic groups in the U.S. differential item functioning analyses using item response theory were conducted among 44,846 U.S. adults drawn from the California Health Interview Survey. Results show that four items (“nervous,” “restless,” “depressed,” and “everything an effort”) varied significantly across races/ethnicities and four items (“nervous,” “hopeless,” “restless,” and “depressed”) varied significantly across l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Although a few studies examined measurement equivalence of an instrument between English-using and Spanish-using Hispanics (e.g., Azocar et al, 2001 ; Hahn et al, 2014 ; Kim et al, 2016 ; Jones, 2006 ), Asian Americans have received little attention mostly due to the lack of data that include sufficient number of participants interviewed/surveyed in Asian languages. The Asian American Quality of Life (AAQoL) survey, which employed multiple strategies to capture cultural and linguistic diversities of Asian Americans (e.g., use of Asian language versions of the questionnaire, bilingual and bicultural research personnel, and community partnerships), included many non-English speaking participants, offering an optimal opportunity to explore measurement equivalence between English and non-English (Chinese, Korean, and Vietnamese) versions of the same instrument.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although a few studies examined measurement equivalence of an instrument between English-using and Spanish-using Hispanics (e.g., Azocar et al, 2001 ; Hahn et al, 2014 ; Kim et al, 2016 ; Jones, 2006 ), Asian Americans have received little attention mostly due to the lack of data that include sufficient number of participants interviewed/surveyed in Asian languages. The Asian American Quality of Life (AAQoL) survey, which employed multiple strategies to capture cultural and linguistic diversities of Asian Americans (e.g., use of Asian language versions of the questionnaire, bilingual and bicultural research personnel, and community partnerships), included many non-English speaking participants, offering an optimal opportunity to explore measurement equivalence between English and non-English (Chinese, Korean, and Vietnamese) versions of the same instrument.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hahn and colleagues (2014) confirmed the absence of DIF by survey language in their development of linguistically equivalent English and Spanish measures of social health. On the other hand, studies focusing on affective and cognitive measures report the presence of DIF between English and Spanish versions of an instrument (e.g., Azocar, Arean, Miranda, & Muñoz, 2001 ; Kim, DeCoster, Bryant, & Ford, 2016 ; Jones, 2006 ), elucidating potential reporting bias that may stem from linguistic differences in nuances and connotations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have developed standardized scales, such as the six-item Kessler psychological scale (K6), for the assessment of psychological distress 2 . Previous clinical research has demonstrated that the K6 has a sensitivity of 0.34 and specificity of 0.96 at a cut-point 13 to identify psychological distress associated with common mental illness 3 , although several studies have reported inconsistent findings on the psychometric properties of the K6 among different general populations 4,5 .…”
Section: Introductionmentioning
confidence: 99%